Magnetic Nanoparticles for Drug Targeting : a Magic Bullet for Cancer Therapy - พวงมะลิ ธีระพงษ์ (KKU Science Journal, 2013)
Ferromagnetic materials exhibit superparamagnetic properties with enhanced magnetic moments when their dimensions are smaller than critical sizes. The magnetic moments are directly proportional to the size of nanoparticles; therefore, the magnetic force is increased with increasing volume. Besides, high response to magnetic force can be observed. Their coercivity is approaching zero making this possible for biological applications. At room temperature these nanoparticles are unable to agglomerate thus reducing embolisation in blood vessels. In magnetic drug targeting, magnetic nanoparticles are coated with therapeutic agents and biocompatible materials including various ligands to enable multifunctionality from a single particle platform. The coated nanoparticles are then injected into the circulatory system and are intentionally directed into the target site by external magnetic field. Releasing of the nanoparticles and conjugated therapeutic agents are controlled by pH or unique molecular signature found on malignant cells. The potential of targeted drug delivery stems from significant advantages as follows : (i) the ability to target specific location in the body; (ii) the reduction of the quantity of drug needed to attain a particular concentration in the vicinity of the target; and (iii) the reduction in the concentration of the drug at non-target sites minimizing severe side effects.